Commentary: Cerebrospinal fluid changes in cattle with rabies or with BoHV-5 meningoencephalitis and its correlation with the severity of CNS inflammatory process. (August 2019) - Yang, Ji-Li; Chen, Teng; Miao, Fa-Ming; You, Li-Xin; Jiang, Hong-Yun; Zhao, Li-Feng; Wei, Yu-Xuan; Liu, Fei; Zhao, Jing-Hui
Highlights: More samples from the natural infection cattle of rabies virus were collected, more findings would be revealed. The molecular characterization and epidemiology analysis of cattle rabies should be constantly investigated in Brazil. The epidemiological data might be the foundation for the control of rabies in the future.